Integration Of Environmental Accounts With National Income: A Review Of Literature. - BORUAH, BHARGAV GAUTAM (The journal of contemporary issues in business and government, 2021)
Environmental accounts bring together economic and environmental information in a common framework for measuring the contribution towards the economy as well as the impact of the economy on the environment. It organize environmental data from different domains by showing the interaction between economic, household and environmental factors, which as a result becomes more informative than national accounts alone. The paper is an attempt to report survey results for framing a better decision by establishing a link between economy and the environmental accounts. This paper is based on certain literature from a limited database.